Computed tomography and anatomy of the abdominal structures in the giant anteater (Myrmecophaga tridactyla) - de Oliveira, Fernanda Gabriela [UNESP]; Schimming, Bruno Cesar [UNESP]; da Costa, Isis Pinto [UNESP]; da Silva, Jeana Pereira [UNESP]; de Lima, Heloísa Coppini [UNESP]; Cardoso, Eduardo Burgarelli Mayrink [UNESP]; da Silva, Suelen Lorena [UNESP]; da Silva Alves, Lidiane [UNESP]; Mamprim, Maria Jaqueline [UNESP] (Wiley, 2023)
The giant anteater (Myrmecophaga tridactyla) is the largest of the Neotropical vermilinguans. This animal is the second mammal most frequently run over on the roads of Cerrado biome, Brazil. Therefore, it is pivotal to know the anatomy of this species to contribute to the clinical care of these animals. Thus, the aim of this study was to identify the anatomical structures in the abdominal region of the giant anteater using computed tomography (CT). For this, the tomographic analysis was performed in sequential order in the craniocaudal direction in five giant anteaters. Moreover, four giant anteater corpses were used for anatomical studies, where two corpses were sectioned in cross sections of approximately 3 cm each, and two animals were dissected to identify the abdominal organs. The association between CT and anatomical study allowed the visualization of anatomical structures found in the abdominal cavity, such as the topographic anatomy facilitates the identification of organs on CT images. The findings of this study demonstrated that CT is a good technique to provide detailed information about the anatomical structures in the abdominal cavity and that this study can be used as CT and anatomical reference for veterinarians who care for wild animals.
Keywords: giant anteater; imaging diagnostic; wildlife; Xenarthra